Prebiotic isomalto-oligosaccharide production from economic crops of Thailand - Saman, Premsuda; Chaiongkarn, Achara; Moonmangmee, Somporn; Artjariyasripong, Suparp (Asia-Pacific Journal of Science and Technology, 2017)
The production of Isomalto-oligosaccharide by fungal fermentation using economic crops such as rice and cassava as substrates was investigated. Solid-state fermentation with Aspergillus oryzae TISTR 3102 was studied to maximise isomalto-oligosaccharides yield. Results show that the fermentation of rice with A. oryzae TISTR 3102 produced the highest concentrations of total reducing sugar (753 mg/g) and free amino nitrogen (33.6 mg/g) together with the highest levels of amylolytic activity (136.4 U/g), α-amylase (52.5 U/g) and α-glucosidase (2.4 U/g). After appropriate fermentation time at the 5-day, both fermented rice and cassava slurries were experimented on further in mashing for the production of syrup. The rice syrup obtained contained the highest amounts of isomaltose, panose and isomaltotriose which were prebiotic isomalto-oligosaccharides.